Research Progress of Cut-Resistant Textile Materials - Zhai, Yanru; Mao, Lizhou; Shen, Yue; Yan, Xuefeng (Frontiers in Chemistry, 2021)
In order to promote the application of cut-resistant textile materials in the field of safety protection, the types, physical properties, advantages and disadvantages and modification technology of common cut-proof textiles and their raw materials are described and compared. This paper introduces the physical properties of cut-proof textile coating materials, analyzes the future development trend of coating materials, and expounds several common evaluation standards of cut-proof textile materials: EN420, EN388, ASTMF-1790 and ISO13997. Some future developments directions of cut-resistant textiles are highlighted.